Staged Management of Severely Displaced Calcaneal Fractures With Transarticular Pinning: A Damage Control Strategy. (November 2021) - Park, Kyeong-Hyeon; Oh, Chang-Wug; Kim, Joon-Woo; Kim, Hee-June; Kim, Dong-Hyun; Kim, Tae-Seong
Background: Severely displaced calcaneal fractures can result in considerable morphology derangement and may be accompanied by soft tissue compromise. Delayed operative restoration of the calcaneal morphology may result in acute retensioning of the damaged soft tissue with associated wound-related complications. In this study, we describe a staged treatment of displaced intra-articular calcaneal fractures that uses temporary transarticular Kirschner wire (K-wire) fixation and staged conversion to definite fixation. Methods: We identified all of the patients who were treated at our institution for calcaneal fractures between 2015 and 2019. A total of 17 patients with 20 calcaneal fractures were selectively treated with 2-stage management. Temporary transarticular K-wire fixation was performed 24 hours after the injury to restore calcaneal morphology and the surrounding soft tissue. After the soft tissue was considered safe, delayed open reduction and internal fixation was performed. The time to definite surgery, radiographic alignment, wound complications, time to radiographic union, and hindfoot American Orthopaedic Foot & Ankle Society (AOFAS) scores were recorded. Results: The average follow-up period was 17 months (range, 12-43). The average Böhler angle increased from a mean of −22 degrees (range, −109 to 25) to 25 degrees (range, 0 to 47) after temporary transarticular K-wire fixation. The mean time from temporary pinning to conversion to definite internal fixation was 20 (range, 10-32) days. There were no immediate postoperative complications. The average time to radiographic union was 13.7 (range, 10-16) weeks. The mean AOFAS score was 87 (range, 55-100). No infections or wound complications were reported during the follow-up period. Conclusion: Temporary transarticular pinning for staged calcaneal fracture treatment is safe and effective in restoring the calcaneal morphology. This novel and relatively simple method may facilitate delayed operation and decrease wound-related complications. Level of Evidence: Level IV, retrospective case series.